2017
DOI: 10.15761/gmo.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of weaning and extubation failure in mechanically ventilated acute ischemic stroke patients

Abstract: Background: Some patients with acute ischemic stroke develop respiratory failure requiring mechanical ventilation. In such patients, traditional weaning parameters poorly predict successful extubation. Failure of extubation increases medical complications. We hypothesize that predictive factors associated with weaning failure can be identified in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The current study found no statistically significant association between weaning failure and mortality with p-value=0.10, which goes in run with Yonaty et al (13) study that was conducted on 158 mechanically ventilated patients planned for weaning and revealed no statistically significant association between weaning failure and mortality with pvalue =0.33.…”
Section: Baptistella and Collegessupporting
confidence: 80%
See 2 more Smart Citations
“…The current study found no statistically significant association between weaning failure and mortality with p-value=0.10, which goes in run with Yonaty et al (13) study that was conducted on 158 mechanically ventilated patients planned for weaning and revealed no statistically significant association between weaning failure and mortality with pvalue =0.33.…”
Section: Baptistella and Collegessupporting
confidence: 80%
“…In contrast to Yu et al (22) found no significant difference between weaning failure and weaning success regarding the length of ICU stay (p =0.166). However, Yonaty et al (13) revealed that the longer duration of hospital stay duration in associated with weaning failure (p <0.01).…”
Section: Keyal Et Almentioning
confidence: 96%
See 1 more Smart Citation